Optimasi Penentuan Material Alat Pemotong Ring Gelas Plastik AMDK: Sebuah Analisis Pendekatan Analytical Hierarchy Process (AHP) - Eko Ari Wibowo; Muhammad Nur Wahyu Hidayah; Eka Samsul Ma’arif; Susanti Sundari; Imam Samsul Ma’arif (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The landfill problem caused by plastic glass water bottle waste has become a serious concern in the last decade. The right processing process can be a solution to these problems, especially in the process of separating plastic glass components. The purpose of this study is to prioritise the main material alternatives used in the plastic glass ring cutter. The required material selection criteria consist of four, namely: material strength, material weight, environmental resistance and cost of raw materials and manufacturing processes. The specified material alternatives are: mild steel (SS41), aluminium and polymer (nylon). Based on the weighting determined by the experts and data processing using the AHP method, the first priority alternative material is aluminium with a value of 0.432 or 43.2%, the second is mild steel (SS41) with a value of 0.367 or 36.7% and the third is polymer (nylon) with a value of 0.201 or 36.7%. Based on these results, the main priority for the use of alternative materials in the AMDK plastic glass ring cutting tool is aluminium.